PROSPECTS OF WASTE TO ENERGY FROM CONTROLLED LANDFILL SYSTEM IN CIREBON, WEST JAVA - Djohar Maknun; Muhimatul Umami (Universitas Bhinneka PGRI, 2024)
This research aimed to examine the potential of waste from controlled landfills a raw material for a Waste-to-Energy (WtE) plant. The research employed the qualitative method with direct observation. Data were analyzed descriptively. The results showed that the composition of waste in Cirebon was mostly dominated by household food waste (52.41%), followed by plastic (15.58%) and paper (8.05%). Based on the amount of existing waste and the projected amount in Cirebon City and Cirebon Regency, the waste can potentially be used as raw material for WtE plant. The energy generated from this waste can be sold to PLN, creating a positive utilization of the waste. It is projected that Cirebon City will produce 1319 m3/day of waste, and Cirebon Regency will produce 4767.65 m3/day (1161.26 tons/day) in 2023. Therefore, further research is needed to develop appropriate, efficient, and environmentally friendly technology for the municipal solid waste management system in Cirebon.